2016
DOI: 10.14701/kjhbps.2016.20.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Case report of solitary giant hepatic lymphangioma

Abstract: A hepatic lymphangioma is a rare benign neoplasm that is usually associated with systemic lymphangiomatosis. A solitary hepatic lymphangioma is extremely rare. Therefore, we present a rare case of a female patient who underwent right hepatectomy for solitary giant hepatic lymphangioma. A 42-year-old female presented to the emergency department with complaint of severe abdominal pain of the right upper quadrant. Abdominal computed tomography showed an approximately 23×30-cm sized, giant, relatively well-defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Hepatic lymphatic malformations (HLM) are extremely rare (8 cases reported in the literature up to 2010 [ 26 ]). They consist of benign cystic dilatations of the liver’s lymphatic spaces, commonly associated with systemic lymphangiomatosis [ 6 , 27 ]. These cysts are lined with endothelial cells and filled with lymph [ 27 ].…”
Section: Other Cystic Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic lymphatic malformations (HLM) are extremely rare (8 cases reported in the literature up to 2010 [ 26 ]). They consist of benign cystic dilatations of the liver’s lymphatic spaces, commonly associated with systemic lymphangiomatosis [ 6 , 27 ]. These cysts are lined with endothelial cells and filled with lymph [ 27 ].…”
Section: Other Cystic Lesionsmentioning
confidence: 99%
“…They consist of benign cystic dilatations of the liver’s lymphatic spaces, commonly associated with systemic lymphangiomatosis [ 6 , 27 ]. These cysts are lined with endothelial cells and filled with lymph [ 27 ]. Three subtypes of HLM are described in the literature: capillary (super-microcystic), cavernous (microcystic), or cystic (macrocystic) [ 6 , 27 ].…”
Section: Other Cystic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review of the literature identified 23 cases of solitary hepatic lymphatic malformations from 1994 to 2020 (13 males and 10 females), with an age range from 22 days to 75 years [ 15 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. According to our review, the management of symptomatic LMs of the liver is still predominantly based on surgical resection [ 15 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , 38 , 40 , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. This can be explained by the fact that the cases described concerned LMs with well-defined profiles and sufficiently distant from vascular or nerve structures, for which surgical approach could guarantee a complete resection and important neurovascular structures sparing.…”
Section: Management and Treatment Optionsmentioning
confidence: 99%
“…When lymphangiomas affect multiple organs, including the liver, spleen, soft tissues, serosa (mesentery), peritoneum, retroperitoneum, and skeletal, the situation is named lymphangiomatosis, which could not be eradicated by surgery but may respond to systemic chemotherapy and radiotherapy with limited efficacy and poor prognosis[ 11 - 13 ]. In addition, solitary lesions in the liver are rare and are further classified into capillary lymphangioma, cystic lymphangioma, and cavernous lymphangioma[ 4 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%